Eruption eaudiobook Supervolcano series, book 1. - Turtledove, Harry (Supervolcano, 2012)
The New York Times bestselling author and "maven of alternate history" (San Diego Union-Tribune) presents a near-future thriller. A supervolcanic eruption in Yellowstone Park sends lava and mud flowing toward populated areas, and clouds of ash drifting across the country. The fallout destroys crops and livestock, clogs machinery, and makes cities uninhabitable. Those who survive find themselves caught in an apocalyptic catastrophe in which humanity has no choice but to rise from the ashes and recreate the world .